Enhancing Public Service Motivation: The Influence of Servant Leadership and Basic Need Satisfaction in Health Center Employees - Muhamad Agung Ali Fikri; Lala Hucadinota Ainul Amri; Multi Nadeak (International Journal of Management and Economic Research (IJOMER), 2024)
Motivating public service employees such as Puskesmas employees, especially in this pandemic era, is very crucial for every Puskesmas unit. Therefore, this study aims to measure the correlation of the effect of servant leadership on public service motivation, both directly and indirectly through the mediation of basic need satisfaction.  Data were collected from 73 health center employees, including doctors, who work at health centers in Tangerang Regency. The research method used was quantitative method and confirmatory survey with the help of SmartPLS 3.0 software. This study shows that servant leadership practices have a positive and significant influence on public service motivation of Puskesmas employees, both directly and indirectly through the mediation of basic need satisfaction.